1986
DOI: 10.1055/s-2007-969254
|View full text |Cite
|
Sign up to set email alerts
|

Oxypeucedanin, a Major Furocoumarin in Parsley,Petroselinum crispum

Abstract: Fresh parsley leaves and roots were analyzed by HPLC and photobiological assay for photoactive furocoumarins. Oxypeucedanin ( 7), not previously reported from parsley, was found to be the major component (70-100 ppm wet weight). Although only moderately photoactive, its high concentration in parsley may be partially responsible for contact photodermatitis. Other photoactive compounds, namely 5-MOP ( 2), 8-MOP ( 3), psoralen ( 1), isopimpinellin ( 4) and imperatorin ( 5) were also present and quantified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…[10][11][12][13] and the following: 5-methoxypsoralen (light-activated) and 8-methoxypsoralen (46, 47) (psoralen, which is carcinogenic by skin painting, and many other mutagenic psoralen derivatives are also present in parsley and celery); p-hydrazinobenzoate and glutamyl p-hydrazinobenzoate (48,49); allyl isothiocyanate (31,32); D-limonene (50); estragole and safrole (45,51); ethyl acrylate and benzyl acetate (52); a-methylbenzyl alcohol (53); caffeic acid (37); sesamol (37); catechol (37). Concentration references are as follows: 5-and 8-methoxypsoralen (17,(55)(56)(57)(58)(59); p-hydrazinobenzoates (in commercial mushrooms) (48,49); sinigrin (38)(39)(40)60); D-limonene (61-63); estragole and safrole (64-67); ethyl acrylate (68); benzyl acetate (69-71), a-methylbenzyl alcohol (23); caffeic acid, chlorogenic acid, and neochlorogenic acid (72)(73)(74)(75)(76)(77)(78)(79)(80) [in coffee (81)]; catechol (83,84); sesamol (85). For mutagenicity and clastogenicity references, see text.…”
mentioning
confidence: 99%
“…[10][11][12][13] and the following: 5-methoxypsoralen (light-activated) and 8-methoxypsoralen (46, 47) (psoralen, which is carcinogenic by skin painting, and many other mutagenic psoralen derivatives are also present in parsley and celery); p-hydrazinobenzoate and glutamyl p-hydrazinobenzoate (48,49); allyl isothiocyanate (31,32); D-limonene (50); estragole and safrole (45,51); ethyl acrylate and benzyl acetate (52); a-methylbenzyl alcohol (53); caffeic acid (37); sesamol (37); catechol (37). Concentration references are as follows: 5-and 8-methoxypsoralen (17,(55)(56)(57)(58)(59); p-hydrazinobenzoates (in commercial mushrooms) (48,49); sinigrin (38)(39)(40)60); D-limonene (61-63); estragole and safrole (64-67); ethyl acrylate (68); benzyl acetate (69-71), a-methylbenzyl alcohol (23); caffeic acid, chlorogenic acid, and neochlorogenic acid (72)(73)(74)(75)(76)(77)(78)(79)(80) [in coffee (81)]; catechol (83,84); sesamol (85). For mutagenicity and clastogenicity references, see text.…”
mentioning
confidence: 99%
“…The concentrations of linear furanocoumarins also have been determined in raw, boiled, and microwaved parsnip root (Ivie et al, 1981) (Table 22) and in fresh and dried parsley (Beier and Ivie, 1985;Chaudhary et al, 1986) (Table 23). Ivie et al (1981) pointed out that consumption of moderate quantities of parsnip root could result in ingestion of appreciable amounts of linear furanocoumarins.…”
Section: Parsley and Parsnipsmentioning
confidence: 99%
“…Their study also demonstrated that these chernicals are stable to cooking. Concentrations of linear furanocoumarins found in parsley by Chaudhary et al (1986) and by Beier and Ivie (1985) are compared in Table 23. There is considerable difference between the two data sets describing the quantities of linear furanocoumarins found in parsley.…”
Section: Parsley and Parsnipsmentioning
confidence: 99%
See 2 more Smart Citations